Damage‐resistance matrix embedding framework: the contradiction between robustness and embedding efficiency. Issue 9 (15th September 2014) - Liu, Weiwei; Liu, Guangjie; Dai, Yuewei
Abstract Matrix embedding schemes based on linear codes have been widely used in the field of steganography, which is an important branch of covert communication. Nevertheless, they appear weak for some conditions of high reliability demand or "active attack" because of the poor robustness. In this paper, with robustness analysis of matrix embedding based on Tanner graph, a general framework of damage‐resistance matrix embedding (DR‐ME) is described to take account of both robustness and embedding efficiency, which has a fair chance to recover the secret message when stego object is partly damaged. The approximated robustness–efficiency bound is derived to reveal the contradiction between robustness and embedding efficiency. Then, based on the parity‐check concatenation of systematic convolutional codes and syndrome‐trellis codes (STCs), we propose the practical damage‐resistance STCs (DR‐STCs). Experimental results show that DR‐STCs are near‐optimal DR‐ME schemes, which can approach the derived upper bound. Copyright © 2014 John Wiley & Sons, Ltd.